Hanbury and Martin, modern equity - Glister, James; Lee, James, 1983- (Sweet & Maxwell, 2021)
Hanbury & Martin: Modern Equity provides an up-to-date and modern account of this challenging area of the law. This twenty-second edition of the long-standing work is the third edition under the present editors. The new edition contains rigorous analysis of the latest in case law and academic debate, with strengthened reference to other common law jurisdictions. Modern Equity continues to be unparalleled in breadth of scope and wealth of detail and remains the authority on equity and trusts law.